MONITORING OF WATER QUALITY IN THE LAKE MARKEERMEER, THE NETHERLANDS - Philiphi de Rozari (Bumi Lestari Journal of Environment, 2009)
Lake Markermeer is a large fresh water lake in the centre of the Netherlands. The actual problem in this lake was its high turbidity. Since Lake Markermeer is categorised as a shallow lake, it is very susceptible for water quality problems. The general objective of this study was to study water quality of Lake Markermeer. Monitoring of water quality was carried out in a 5 months period from November, 2007 until March, 2008. For this research, surface water was firstly sampled at 66 representative sites; parameters measured were: pH, EC, temperature, turbidity, DO, Secchi depth, P total, N total, chlorophyll and Silica total. The monitoring was continued every two weeks at two fixed sampling sites referred to as STA and STB with the same previous parameters excluding total. Statistical t-test analysis was utilised to compare the value of each parameter between two sampling stations. Result of water quality measurement showed that variability of surface water quality in the Lake Markermeer could be explained as follows: for pH, conductivity, temperature and dissolved oxygen (DO) no significant variation was found among sampling sites (coefficient of variation, CV ? 10%). On the other hand, for turbidity, Secchi disk depth, P total, N total, chlorophyll-a and silica total, ranges between minimum and maximum values were significantly larger (CV > 10%). The result of the turbidity, Secchi disk depth, N total, P total and chlorophyll-a at the two fixed sampling stations were much diverse during the sampling period.